2020
DOI: 10.1097/md.0000000000023186
|View full text |Cite
|
Sign up to set email alerts
|

Trends and diagnostic value of D-dimer levels in patients hospitalized with coronavirus disease 2019

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Additional research could help us to understand this heterogeneity further, Yao et al 19 retrospectively analyzed D-dimer upon admission and identified a cut off value >2.14 mg/ml predicting in-hospital mortality with a sensitivity of 88.2% and specificity of 71.3%. Creel-Bulos et al 37 rendered a comprehensive observation of D-dimer trajectories and represented a highly predictive value of a rise in D-dimer (>2000 ng/ml) of any 24 hours within 10 days with 75% sensitivity and 74% specificity while baseline value was not associated with VTE. A Chinese study composed of 1114 patients 38 mentioned the meaningfulness of last D-dimer test before discharge or death in prognosing death using a cut off value of 2.025 mg/L rather than the first test at admission, the AUC of which was 0.909.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research could help us to understand this heterogeneity further, Yao et al 19 retrospectively analyzed D-dimer upon admission and identified a cut off value >2.14 mg/ml predicting in-hospital mortality with a sensitivity of 88.2% and specificity of 71.3%. Creel-Bulos et al 37 rendered a comprehensive observation of D-dimer trajectories and represented a highly predictive value of a rise in D-dimer (>2000 ng/ml) of any 24 hours within 10 days with 75% sensitivity and 74% specificity while baseline value was not associated with VTE. A Chinese study composed of 1114 patients 38 mentioned the meaningfulness of last D-dimer test before discharge or death in prognosing death using a cut off value of 2.025 mg/L rather than the first test at admission, the AUC of which was 0.909.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] In fact, D-dimer levels in the first 7 days of disease and the rate of change of D-dimer levels have been shown to reliably predict VTE. 52 Other thrombotic complications, including stroke and cerebral venous sinus thrombosis, 14,15 MI, [16][17][18] acute limb ischemia, 19 acute kidney injury, 20 and ischemic colitis, 21 have been reported in patients with COVID-19. Mechanistically, the markedly elevated levels of D-dimer in patients with fibrinolysis shutdown might represent local thrombosis in the microvasculature (eg pulmonary and renal) that are not consistently captured on whole-blood assays.…”
Section: Thrombotic and Bleeding Complica-tions In Covid-19-associated Fibrino-lysis Shutdownmentioning
confidence: 99%
“…Similarly, we showed that initial D-Dimer and maximum D-Dimer correlated with clot development but also mortality. The lack of D-Dimer association with mortality in the Creel-Bulos et al (2020) study may be due to a sample size limitation. Huang et al, showed that an initial D-Dimer = 1 ug/mL correlates with increased risk of mortality.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, analysis of the maximum and minimum levels of important lab parameters indicated that, in addition to the importance of the initial D-Dimer to screen patients that present with coagulopathy and are at higher risk of mortality, the maximum D-Dimer during hospitalization was also associated with mortality. Creel-Bulos et al (2020) demonstrated that the D-Dimer maximum, magnitude and rate of rise in the first 10 days of admission correlated with VTE but not mortality in a cohort of 115 COVID-19 + inpatients. Similarly, we showed that initial D-Dimer and maximum D-Dimer correlated with clot development but also mortality.…”
Section: Discussionmentioning
confidence: 92%